PENGARUH PRODUK DOMESTIK BRUTO (PDB) TERHADAP PEMBIAYAAN BANK UMUM SYARIAH (BUS) DAN UNIT USAHA SYARIAH (UUS) TAHUN 2010-2014 (PENERAPAN ANALISIS REGRESI DATA POOLING) - Hamni Fadlilah Nasution (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2017)
The main function of BUS / UUS is not much different from conventional banks that collect funds from the public and then channel them back (intermediate). In practice, Islamic banks channeling funds it received in the form of financing, both venture capital financing as well as for consumption. Financing is providing facilities for provision of funds to support the planned investment is based on an agreement between the bank and other parties who require the financed party to return the money or the charges after a certain period of time in exchange or for the results. This study aims to determine the effect of gross domestic product to finance the BUS / UUS. The data used pooling is data. Data pooling with the category of 5 years and 9 sectors studied. analysis is the result of estimation fixed effect. The results showed PBD affect the financing BUS / UUS. , the effect on the GDP amounted to 95.68 percent financing. As well as the remaining amount of 4.32 percent is influenced by other variables not examined in this study. The most high-elasticity sector financing is LGA sector (electricity, gas and water), while the lowest elasticity IDS financing is a sector (manufacturing industry)